Clinical Evaluation of Acanthosis Nigricans and Its Correlation with Endocrine, Metabolic and Nutritional Factors in Gujarat,India: Life Sciences-Pharmacology - Sohan A Patel; Jayant B Dave; Timir Y Mehta (International Journal of Life Science and Pharma Research, 2022)
Acanthosis nigricans (AN) refers to the velvety, black hyperpigmentation in flexures usually on the neck and axillae. AN is associated with multiple endocrinopathies and insulin resistance is reported to be a common denominator among them. The aim of the study was to identify the correlation of metabolic factors (Serum glucose, lipid profile), endocrine factors (TSH, serum insulin), and nutritional factors (vitamin B12, Ferritin) in AN patients in Aravalli district of Gujarat state. A total of Seventeen Patients (11 male and 6 female) were included in the study History, clinical observations, physical parameters, and biochemical tests were noted in AN patients and correlation of some likely factors with AN was explored. The age was 28.41±15.09 years for AN group and 35.45±8.74 years for control group. The mean BMI was found to be higher in AN at 1 % level of significance (P = 0.007) implying that overweight/obesity is associated with AN. The mean TSH value was found to be higher in AN than control group at 5 % level of significance (P = 0.0115) implying that hypothyroidism (elevated TSH value) is associated with AN. The 45.45 % patients had higher blood glucose levels and some of the patients had higher level of insulin. The mean lipid profile, vitamin B12 and serum ferritin were found to be at non-significance level. All statistical tests were performed using graph pad prism software (version 5.0). Positive correlations were observed between higher fasting glucose and hyperinsulinemia with AN and others factors such as metabolic and endocrine like overweight/obesity, hypothyroidism, higher glucose and serum insulin with AN. This implies that AN can serve as a marker for detecting hyperinsulinemia and hypothyroidism. Some of the parameters like, Serum lipid profile, vitamin B12 and ferritin levels could not be correlated to AN. Thus, patients with AN can be targeted for lifestyle and behavioral modifications at an early stage to avoid the serious consequences of AN.